Advances in the Synthesis and Applications of Mussel-Inspired Polymers. (2nd January 2023) - Mu, Youbing; Sun, Qian; Li, Bowen; Wan, Xiaobo
Abstract: Learning from nature and promoting original design concept is a significant way to develop functional materials with outstanding performance. Even since the discovery of the role of DOPA residues in the strong adhesion ability of mussel foot-byssus proteins (Mfps), numerous efforts have been devoted into the design of mussel-inspired polymers and many outstanding results have been achieved. Herein, this review is aimed to summarize the recent progress in mussel-inspired polymers in the last decade, including further explorations in the structure and functionality of Mfps, the design trend and driving forces for mussel-inspired polymers, and the applications and prospects for functional mussel-inspired polymers. We anticipate that this review can provide some guidance for researchers to explore novel biomimetic materials.